Biophysical regulation of vascular differentiation and assembly - Gerecht, Sharon; SpringerLink (Online service). (New York Springer, 2011)
The ability to grow stem cells in the laboratory and to guide their maturation to functional cells allows us to study the underlying mechanisms that govern vasculature differentiation and assembly in health and disease. Accumulating evidence suggests that early stages of vascular growth are exquisitely tuned by biophysical cues from the microenvironment, yet the scientific understanding of such cellular environments is still in its infancy. Comprehending these processes sufficiently to manipulate them would pave the way to controlling blood vessel growth in therapeutic applications. This book assembles the works and views of experts from various disciplines to provide a unique perspective on how different aspects of its microenvironment regulate the differentiation and assembly of the vasculature. In particular, it describes recent efforts to exploit modern engineering techniques to study and manipulate various biophysical cues. Biophysical Regulation of Vascular Differentiation and Assembly provides an interdisciplinary view of vasculature regulation by various biophysical cues and presents recent advances in measuring and controlling such parameters. This book will be of interest to biologists, biophysicists and engineers who work with vascular differentiation and assembly.
Preface -- Embryonic and Adult Stem Cells in Vasculogenesis and Angiogenesis -- Extracellular Matrix and Matrix Metalloproteinase in Vascular Morphogenesis -- Scaffolding for Three-Dimensional Embryonic Vasculogenesis -- Matrix Viscoelasticity and Remodeling During 3D Vascular Assembly -- Biomechanical Properties of Implanted Scaffolds Affect Human Blood Vessel Formation From Circulating Endothelial Colony Forming Cells -- Oxygen Regulation of Adult Angiogenesis -- Hypoxia During Embryonic Vascular Development and Differentiation -- Three-Dimensional Regulation During Cancerous Angiogenesis -- Microfluidics to Control Shear and Oxygen Flow for Vascular Differentiation -- Cyclic Strain and Surface Shape for Engineered Vasculature Constructs -- Matrix Topography and Viscoelasticity Guide Vascular Assembly.
Electronic reproduction.
Keywords: Stem cells; Blood-vessels -- Growth; Biophysics; Biomedical engineering; Neovascularization -- Regulation; Blood-vessels -- Growth -- Regulation; Cell differentiation; Electronic books